Analysis of genetic diversity in two different shell colors of the giant triton snail (Charonia tritonis) based on mitochondrial COI sequences - Cen, Xitong; Zhang, Gege; Liu, Huiru; Yao, Gaoyou; Xiong, Panpan; He, Maoxian; Liu, Wenguang (Frontiers in Marine Science, 2023)
The giant triton snail (Charonia tritonis) is widely distributed in tropical coral reefs in the Indo-West Pacific. Its distribution areas in China include the Penghu Islands, Hengchun Peninsula, and Xisha Islands. In this study, we use Multivariate Analysis of Variance (MANOVA) to compare the live weight and shell length between different shell colors of C. tritonis. In addition, we conducted sequence analysis of the mitochondrial cytochrome oxidase (COI) gene to assess the affinity of C. tritonis with two different shell colors based on the sample we obtained. Then, we constructed phylogenetic trees using the maximum likelihood (ML) and Bayesian Inference methods, and constructed haplotype network diagrams. In addition, we performed Tajima’s D and Fu’s neutrality tests. The results show that The Partial mitochondrial COI sequences of 28 C. tritonis were all 603 base pairs in length, and seven haplotypes were detected from the samples, besides, the gene flow was calculated to be 11.78, the genetic differentiation coefficient was 0.02078. Our results indicated that the population size of C. tritonis remained relatively stable. Besides, the genetic and size differentiation between the two different shell colors was small, and individuals of C. tritonis with different shell colors belong to the same genetic clade. In fact, the two morphotypes could not be distinguished by both genetic and morphometric data. The mitochondrial COI gene fragments of the two different shell colors were sequenced and analyzed to accumulate information about the population genetics of C. tritonis and to provide a scientific basis for the conservation of its species resources.The giant triton snail (Charonia tritonis) is widely distributed in tropical coral reefs in the Indo-West Pacific. Its distribution areas in China include the Penghu Islands, Hengchun Peninsula, and Xisha Islands. In this study, we use Multivariate Analysis of Variance (MANOVA) to compare the live weight and shell length between different shell colors of C. tritonis. In addition, we conducted sequence analysis of the mitochondrial cytochrome oxidase (COI) gene to assess the affinity of C. tritonis with two different shell colors based on the sample we obtained. Then, we constructed phylogenetic trees using the maximum likelihood (ML) and Bayesian Inference methods, and constructed haplotype network diagrams. In addition, we performed Tajima’s D and Fu’s neutrality tests. The results show that The Partial mitochondrial COI sequences of 28 C. tritonis were all 603 base pairs in length, and seven haplotypes were detected from the samples, besides, the gene flow was calculated to be 11.78, the genetic differentiation coefficient was 0.02078. Our results indicated that the population size of C. tritonis remained relatively stable. Besides, the genetic and size differentiation between the two different shell colors was small, and individuals of C. tritonis with different shell colors belong to the same genetic clade. In fact, the two morphotypes could not be distinguished by both genetic and morphometric data. The mitochondrial COI gene fragments of the two different shell colors were sequenced and analyzed to accumulate information about the population genetics of C. tritonis and to provide a scientific basis for the conservation of its species resources.